2018
DOI: 10.1021/jacs.8b05354
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Unprecedented Hydrazine-Forming Machinery in Bacteria

Abstract: Recent studies described several different routes that facilitate nitrogen-nitrogen bond formation in natural product biosynthesis. We report herein the identification of unprecedented machinery for hydrazine formation involved in the biosynthesis of s56-p1, a dipeptide natural product with a unique hydrazone unit. The gene cassette comprising this machinery is widespread across several bacterial phyla, highlighting the overlooked potential of bacteria to synthesize hydrazine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
140
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(148 citation statements)
references
References 42 publications
7
140
1
Order By: Relevance
“…As an example, N5 of ornithine is hydroxylated by a flavin‐dependent enzyme (KtzI) before N−N bond formation promoted by a heme enzyme (KtzT, Figure S1 in the Supporting Information) . Similarly, N 6 ‐hydroxylysine is conjugated to glycine followed by intramolecular nucleophilic attack from the glycine amino group catalyzed by a fusion protein (Spb40) consisting of a cupin and a methionyl‐tRNA synthetase‐like protein (Figure S1) …”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…As an example, N5 of ornithine is hydroxylated by a flavin‐dependent enzyme (KtzI) before N−N bond formation promoted by a heme enzyme (KtzT, Figure S1 in the Supporting Information) . Similarly, N 6 ‐hydroxylysine is conjugated to glycine followed by intramolecular nucleophilic attack from the glycine amino group catalyzed by a fusion protein (Spb40) consisting of a cupin and a methionyl‐tRNA synthetase‐like protein (Figure S1) …”
Section: Figurementioning
confidence: 99%
“…It is notable that tri26–31 are homologous to the gene cassette spb38–43 , which was found to be essential for the biosynthesis of the glyoxylate hydrazine unit in s56‐p1 . This thus suggests that, in a triacsin, at least one N−N bond is formed through the action of Tri28, the homologue of Spb40 consisting of a cupin and a methionyl‐tRNA synthetase‐like protein.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…[35] Enzymes encoded by the latter set of genes have been shown to catalyze the transformation of lysine and glycine to give hydrazino acetic acid (20) enroute to s56-p1 (Scheme 2B). [35] Hence,h ydrazine formation may also be involved in the construction of the pyrazole group of formycins [33] and perhaps pyrazofurin as well (Scheme 2C). If correct, this hypothesis suggested acriterion by which the pyrazofurin gene cluster might be identified in ag enome-wide search of the producing strain.…”
mentioning
confidence: 99%
“…B Formationo fhydrazino acetic acid (20) in the biosynthesis of s56-p1 (21). [35] C Possible involvement of ForJ/K/ La nd PyfG/H/I in hydrazine assembly in formycin and pyrazofurin biosynthesis,respectively. bioinformatic analysis collectively suggested that the pyf cluster encodes the enzymes of pyrazofurin biosynthesis.…”
mentioning
confidence: 99%